Climate and landscape changes enhance the global spread of a bloom-forming dinoflagellate related to fish kills and water quality deterioration. (December 2021) - Lacerda Macêdo, Rafael; Clara Sampaio Franco, Ana; Russo, Philip; Collart, Tim; Mammola, Stefano; Jeppesen, Erik; Wyss Castelo Branco, Christina; Neves dos Santos, Luciano; Rocha, Odete
Graphical abstract: Highlights: Combined pressures in the invasion success of Ceratium furcoides were investigated. Niche modelling and habitat-relatedness were used to predict future areas at risk. Model show an overlap between future suitable areas and dam construction projections. Dams and climate change will interplay in the outcomes of invasion success. Abstract: Global inland water biodiversity is under mounting stress facing future scenarios of climate change, biological invasions, pollution, diversion, damming of rivers, and increase of water abstractions. Apart from having isolated effects, all these stressors threats act synergistically and thus pose additional emerging threats to biodiversity and ecosystem services. Native to Northern Europe, the nuisance and potential toxic dinoflagellate Ceratium furcoides (Levander) Langhans 1925 is a silent invader that blooms in freshwater systems; it has one of the most rapid spread rates globally. We propose a framework to determine the worldwide most vulnerable areas for the invasion by C. furcoides shortly (2041–2060) by combining future scenarios of climate change (a proxy for invasiveness) derived from ecological niche models with future dam construction data (a proxy for invasibility). The nine models applied in four future scenarios of greenhouse gas emission from Coupled Model Intercomparison Project Phase 6 showed a general increase in areas suitable for the invasion success of C. furcoides . High susceptibility overlapped with areas densely occupied by large and medium-size dams and future dam construction projects. Considering that C. furcoides can reproduce from a single cell, produces resistant stages, and has several strategies to cope with local environmental constraints, early detection protocols, and mitigation actions are urgently needed to avoid biodiversity declines related to this invader.